An Empirical Study on Verbal Violence Experiences among Bank Consulting - et. al., Sang-Jin Lee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The development of smart devices and the products of ICT are becoming a medium for verbal abuse, causing serious problems in bank counseling. Research on verbal abuse in the bank counseling process started at call centers, and as the damage caused by verbal abuse is known, a lot of research were rapidly conducted. These include the understanding of verbal violence and the closest group in which verbal violence can occur over a long period of time and the horizontal and vertical forms of verbal violence. There are also multilateral studies to identify the causes of verbal violence and to reduce verbal violence. The scope of verbal violence also varies with definition, phenomenon, type, cause, effect, and factor. In the early days of the study of verbal violence, definitions and types were central. This study focuses on analyzing the relationship of the impact on professional self-concept through psychological exhaustion of verbal violence experiences during bank counseling. Verbal violence is categorized as violence against people who are not related to them and those who are related to them. Verbal violence against irrelevant people is an impromptu violence situation between the perpetrator and the victim during various counseling processes. It refers to violence committed against others during counseling through cyberspace and various media. Personal violence in the counseling process tends to be neglected because the substance is not clear, but the damage is continuing and increasing. Although various psychological studies have been conducted on real violence, there are no studies related to psychological exhaustion and professional self-concept. The factors that determine the verbal violence experience are the violence experience, the violence victim experience, and the violent attitude. The collected data were analyzed by Smart PLS 2.0 using structural equations. The summary of the study is as follows. First, the experience of violence had a significant impact on psychological exhaustion. Second, the experience of violence damage had a significant impact on psychological exhaustion. Third, violent personality had a significant effect on psychological exhaustion. Fourth, psychological exhaustion had a significant impact on professional self-concepts. To solve the problem of overcoming professional self-concepts, differentiated efforts in the experience of violence, violence victimization, and violent attitude are needed in consideration of verbal violence experiences. Related organizations seeking to address verbal violence need to study various opinions on the causes of verbal violence behavior.